PRODUCTION AND CHARACTERIZATION OF WASTE MASK REINFORCED POLYESTER COMPOSITE - Demirel, Maruf Hurşit; Aydoğmuş, Ercan (My University, 2022)
In this research, waste masks (WM) that pollute the environment have been evaluated in the polyester composite. Some physical and chemical properties of the obtained composite have been characterized. In particular, its density, Shore D hardness, thermal conductivity, thermal stability, and porosity have been determined. Waste masks were collected, disinfect, ground, dried and added into unsaturated polyester (UP) at the rates of 0 %, 2 %, 5 %, 7 %, and 10 % by mass as a filler. Mask wastes were reinforced to the unsaturated polyester in certain proportions and were homogenized thoroughly for 10 minutes at a mixing speed of 1000 rpm. Then, the chemical reaction has been carried out with the help of methyl ethyl ketone peroxide (MEKP) and cobalt octoate (Co Oc) catalysts. The chemical bond structure of the produced polyester composites was determined by Fourier transform infrared spectrophotometer (FTIR). According to the results, both density and Shore D hardness of the composites decreased as the WM ratios in the composites increased. It has been evaluated that the mechanical strength of the polyester composite and porosity raises with increasing WM ratio. The increase in WM by mass in the polyester composite raises thermal conductivity and activation energy.
Keywords: Thermal conductivity; Activation energy; Porosity; Polyester composite; Waste mask